2017
DOI: 10.3892/ijo.2017.4233
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of acute myeloid leukemia samples from adult patients with AML-M1 and -M2 through boutique microarrays, real-time PCR and droplet digital PCR

Abstract: Acute myeloid leukemia (AML) is the most common and severe form of acute leukemia diagnosed in adults. Owing to its heterogeneity, AML is divided into classes associated with different treatment outcomes and specific gene expression profiles. Based on previous studies on AML, in this study, we designed and generated an AML-array containing 900 oligonucleotide probes complementary to human genes implicated in hematopoietic cell differentiation and maturation, proliferation, apoptosis and leukemic transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 65 publications
8
60
0
Order By: Relevance
“…Associated diseases included Bleeding Disorder, Platelet-Type, 11(BDPLT11) and Mitochondrial Complex I Deficiency. FCER1G also engaged in many immune responses and played a tumor-promoting role in many kinds of tumors, such as meningioma, Clear cell renal cell carcinoma (ccRCC), childhood leukemia and Acute Myeloid Leukemia(AML) [12,14,15,30]. It was also reported that the demethylation of FCER1G was induced by IL15 in the NKp30+CD8+ T cell population exhibiting high natural killer-like antitumor potential [31].…”
Section: Discussionmentioning
confidence: 99%
“…Associated diseases included Bleeding Disorder, Platelet-Type, 11(BDPLT11) and Mitochondrial Complex I Deficiency. FCER1G also engaged in many immune responses and played a tumor-promoting role in many kinds of tumors, such as meningioma, Clear cell renal cell carcinoma (ccRCC), childhood leukemia and Acute Myeloid Leukemia(AML) [12,14,15,30]. It was also reported that the demethylation of FCER1G was induced by IL15 in the NKp30+CD8+ T cell population exhibiting high natural killer-like antitumor potential [31].…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect has been hypothesised to be an adaptation mechanism in cancer cells to support the biosynthetic requirements of rapid proliferation. Alpha-enolase expression has been shown to be altered at the mRNA and/or protein level in a range of tumours [ Table 1], and generally upregulated in most, including acute myeloid leukaemia (AML), glioma, melanoma, lymphoma, and colorectal, endometrial, gastric, head and neck, liver, ovarian and pancreatic cancer [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Alpha-enolase Expression Is Altered In Tumours and Varies Wimentioning
confidence: 99%
“…Microarray Increased [4] Breast cancer Breast cancer tissue with adjacent matched normal tissue (n = 24)…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As for the possible explanations to our results, it might include: 1) lncRNA RP4-576H24.2 may promote development and progression of AML through regulating multiple downstream genes as displayed in our RNA sequencing results, in which several genes regulated by lncRNA RP4-576H24.2 are reported to participate in the pathogenesis of leukemia, such as PTPRJ, FCN1, KLF4, G0S2, and LILRB2. [28][29][30][31][32] Therefore, ln-cRNA RP4-576H24.2 might promote the development or progression of AML by mediating the leukemia pathology-related genes, such as PTPRJ, FCN1, KLF4, G0S2, and LILRB2; 2) our further cell experiments disclosed that lncRNA RP4-576H24.2 promoted proliferation while inhibited apoptosis of two AML cell lines, indicating that lncRNA RP4-576H24.2 might aggravate the progression of AML through regulating AML cell functions.…”
mentioning
confidence: 87%